2022
DOI: 10.3390/ijms23042296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Filler Contents and Printing Directions on the Mechanical Properties for Photopolymer Resins

Abstract: Photopolymer resins are widely used in the production of dental prostheses, but their mechanical properties require improvement. We evaluated the effects of different zirconia filler contents and printing directions on the mechanical properties of photopolymer resin. Three-dimensional (3D) printing was used to fabricate specimens using composite photopolymers with 0 (control), 3, 5, and 10 wt.% zirconia filler. Two printing directions for fabricating rectangular specimens (25 mm× 2 mm× 2 mm) and disk-shaped sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…Many factors could lead to increased flexural strength, such as size, shape, concentration of filler, homogenous distribution within resin matrix, and the silanization process [ 17 ]. A previous study showed [ 39 ] ZrO 2 NPs added in different concentrations (3, 5, and 10 wt.%) and stated that as the concentrations increased the flexural strength increased up to 5% then an insignificant decrease occurred as the concentration increased up to 10%. The increase in flexural strength with ZrO 2 NP-modified ASIGA was concentration-dependent; as the concentrations increased, the flexural strength increased in ASIGA resin while in NextDent the highest was reported with 1%, without a significant difference in the 3 and 5% groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors could lead to increased flexural strength, such as size, shape, concentration of filler, homogenous distribution within resin matrix, and the silanization process [ 17 ]. A previous study showed [ 39 ] ZrO 2 NPs added in different concentrations (3, 5, and 10 wt.%) and stated that as the concentrations increased the flexural strength increased up to 5% then an insignificant decrease occurred as the concentration increased up to 10%. The increase in flexural strength with ZrO 2 NP-modified ASIGA was concentration-dependent; as the concentrations increased, the flexural strength increased in ASIGA resin while in NextDent the highest was reported with 1%, without a significant difference in the 3 and 5% groups.…”
Section: Discussionmentioning
confidence: 99%
“…ZrO 2 NPs could be a suitable reinforcement method for 3D printing material [ 39 ]. To the best of the authors’ knowledge, no previous studies have investigated the effect of the addition of ZrO 2 NPs on the properties of 3D-printed resins for denture-base fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…ZrO 2 is a biocompatible metal oxide with superior surface hardness, strength, and fracture toughness [ 51 , 52 ]. ZrO 2 NPs have been demonstrated as a suitable reinforcing material for 3D-printed PMMA [ 53 ]. Furthermore, ZrO 2 has thermal stability, corrosion resistance, and antibacterial and antifungal effects on Aspergillus niger and C. albicans [ 39 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the polymethyl methacrylate (PMMA) resin has been widely used as a material for dentures and temporary crowns. Three-dimensional printing has also been used in the dental field, and new dental materials, such as photopolymers, have been employed [ 18 ]. However, the mechanical properties of photopolymers alone are inadequate; hence, satisfying the requirements of ISO standards is difficult.…”
Section: Introductionmentioning
confidence: 99%